Length-weight relationship of two commercially important marine fishes in Central Visayas, Philippines - Resullar, Karizza Bea P.; Arceo, Hazel O. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2021)
Most of the coastal communities in developing nations highly depend on pelagic fishes for livelihoods and food security. The decline in their population can have economic and ecological effects, such that understanding their growth parameters is important. These parameters are of great help in providing information about the general well-being of fishes and their fitness. Many studies about length-weight relationships (LWRs) of fishes have already been conducted in several countries. However, only a few have been done in the Philippines. Selar crumenophthalmus (big eye scads) and Decapterus kurroides (red tail scads), both belonging to the Family Carangidae, are among the most common pelagic species found in commercial fish landings in Cebu, Philippines. This study aimed to: a) evaluate the length-weight relationship of these two commercially important marine species; b) determine the condition factor of each species; and, c) identify possible factors that influenced their growth parameters. The length-weight relationship was carried out for 86 fish samples of the two species (56 for S. crumenophthalmus and 30 for D. kurroides). The total length and weight for S. crumenophthalmus ranged from 16.6 to 25.4 cm (with a mean of 19 cm) and 53 to 250 g (with a mean of 96.5 g), respectively. Meanwhile, the total length measured for D. kurroides ranged from 18.1 to 24.1 cm (with a mean of 20.97 cm), and its total weight ranged from 64.6 to 153.7 g (with a mean of 94.24 g). S. crumenophthalmus showed positive allometric growth (b=3.40) while Decapterus kurroides indicated an isometric growth pattern (b=3.03). Linear regression analysis showed high positive correlation between length and weight for the two species, with r2 ranging from 0.8564 to 0.9688 (p<0.05). The condition factors for S. crumenophthalmus and D. kurroides were 1.350 and 1.004, respectively, which implies that both species are in good condition. The results of this study provide information that can be applied to enhance fisheries management and conservation of these two commercial fish species.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. July 2021